Analysis and control of surge pressure in pumping mains - Lu, Zhanke. (2008)
When flow velocity in a piping system is varied rapidly as may be caused by valve or pump operations, pressure waves associated with the compressibility of the liquid are generated which propagate at close to the speed of sound. The transient pressures are commonly referred to as pressure surges or water hammer. This project reviews the physics and mathematics behind the analyses of water hammer in pipe networks, and the common control measures and devices to protect the pumping mains against excessive surge pressures. The relative merits of different control strategies for various common pumping applications and configurations are evaluated.